Parental report of the association between screen time and social emotional development of children aged 18 and 36 months old in the district of Gombak, Malaysia / Catherine Thamarai Arumugam - Catherine Thamarai, Arumugam (2021)
The increasing popularity of screen-based media has raised public health concern on potential effects of their excessive usage among developing children. The World Health Organization (WHO) and American Academy of Pediatrics (AAP) call for limitation of screen time to one hour per day for children aged two to five years old and children below the age of two are encouraged for screen time avoidance. This study is aimed to determine the influence of screen-based media on early childhood social emotional development from an ecological techno-subsystem perspective. Divided into two phases, the first phase of study involves translation into Malay language and validation of four instruments used in the second phase of study. The “Ages and Stages Questionnaires: Social-emotional”, 2nd edition (ASQ:SE-2) 18-Month and 36-Month intervals are instruments that assess the dependent variable of the study – social emotional development. Other three instruments assess independent variables of the study, namely the “Parent Problematic Digital Technology Use” and “Media and Technology Usage and Attitudes Scale”, both of which measure parental media behaviour and “Technology Related Parenting Scale” which measures home media environment. Second phase of this research work is a cross-sectional study that probes into the association of child screen time and other independent variables with social emotional development. Study duration of proposal development to report writing was more than two years from August 2018 to December 2020. Internal consistency and reliability of instruments were tested on 100 and 60 respondents, respectively in the first phase from the district of Gombak, Malaysia. Construct validity through factor analyses for Parental Media Behaviour and Home Media Environment (Malay language) scales were tested on 150 subjects. For second phase of study, cluster sampling technique was used to recruit 600 respondents from five health clinics in Gombak, Malaysia. Data collection was done via self-administered questionnaires distributed to Malaysian parents of children aged 18 and 36 months old iv brought to primary care health clinics for their routine medical examination. Screen time was measured using Global Time Estimate method. Results from phase I of study shows all instruments display good psychometric properties. Phase II indicates 27.8% children documented exposure to screen-based media within first year of life. Mean screen time per day was found to be 141.7 minutes (SD 131.6). Non-adherence to screen time recommendation was recorded by 82.2% toddlers. The odds of children with excessive screen time to have poor mastery of social emotional development is 2.5 times higher than children adhering to screen time recommendations, with association persisting after adjustment to confounders (adjusted odds ratio 2.50, 95% CI: 1.07 - 5.86). This study contributes by producing cross-culturally adapted questionnaires on developmental screening, parental media behaviour, and home media environment which can be utilized in the local setting. This research work which has identified non-adherence to screen time recommendations as risk factor to early childhood social emotional development is hoped to pave the way for foundation of a national screen time policy which advocates for mindful usage of screen-based media among young children and their families. Keywords: screen-based media, screen time, early childhood social emotional development